Supporting free throw situations of basketball players with augmented reality - Kahrs, L. A.; Raczkowsky, J.; Manner, J.; Fischer, A.; Wörn, H. (International Journal of Computer Science in Sport, 2006)
This article presents our system for supporting basketball players with enhanced training information using augmented reality. A calibrated head mounted display guaranties the precise overlay of real environment and virtual objects. Visual information of the ideal and actual parabola and their deviation can be displayed. The setup is limited momentarily on free throw situations.